The Influence of Internal Village Development Strategies Increase Village Income Through Village Owned Business Entity (Bumdes) in the Village Sei Red, Tanjung Morawa District Deli Serdang Regency - Yuni Andri Ekawati; Dian Purnama Sari (International Journal of Economics (IJEC), 2022)
This study aims to determine whether the village development strategy has an effect on increasing village income in Sei Merah Village, Kec . Tj Morawa . The method used in this study is a quantitative method with several tests, namely reliability and simple linear regression . Based on the results of the primary data regression which was processed using SPSS 1 8 , the following simple linear regression equation was obtained : Y : 21.622 + 0.704X. Based on these data, it can be determined that the size of the t table is 2,003 and it is known that the village development strategy variable has a t count of 5.608, when compared to the t table, the result is 5.608 > 2.003, so it can be concluded that the village development strategy variable has a significant effect on the variable of increasing village income. Based on the results of the regression calculation of the coefficient of determination of the summary model in the table above, it can be seen that the coefficient of determination (R square) obtained in this study is 0.360. This means that 36% of the variables of increasing village income can be influenced by the variables of village development strategies. While the remaining 64% can be influenced by other independent variables that are not included in the study.